Room to Breathe: The Impact of Oxygen Rationing on Health Outcomes in SARS-CoV2 - Goyal, Daniel K.; Mansab, Fatma; Bhatti, Sohail (Frontiers in Medicine, 2021)
As the primary surge of COVID-19 wanes in many countries, it is important to reconsider best practice. More cases, probably the majority of cases, are yet to come. Hopefully during this next phase we will have more time, more resources and more experience from which to affect better outcomes. Here, we examine the compromised oxygen strategy that many nations followed. We explore the evidence related to such strategies, and discuss the potential mortality impact of delaying oxygen treatment in COVID-19 pneumonia.